The Synergistic Influence of Polyflavonoids from Citrus aurantifolia on Diabetes Treatment and Their Modulation of the PI3K/AKT/FOXO1 Signaling Pathways: Molecular Docking Analyses and In Vivo Investigations - Mohamed A. Hassan; Ghada M. Abd Elmageed; Ibtehal G. El-Qazaz; Doaa S. El-Sayed; Lamia M. El-Samad; Heba M. Abdou (MDPI AG, 2023)
This study was aimed at probing the modulatory influence of polyflavonoids extracted from Citrus aurantifolia, lemon peel extract (LPE-polyflavonoids), on attenuating diabetes mellitus (DM) and its complications. HPLC investigations of the LPE exhibited the incidence of five flavonoids, including diosmin, biochanin A, hesperidin, quercetin, and hesperetin. The in silico impact on ligand-phosphatidylinositol 3-kinase (PI3K) interaction was investigated in terms of polyflavonoid class to explore the non-covalent intakes and binding affinity to the known protein active site. The drug likeness properties and pharmacokinetic parameters of the LPE-polyflavonoids were investigated to assess their bioavailability in relation to Myricetin as a control. Remarkably, the molecular docking studies demonstrated a prominent affinity score of all these agents together with PI3K, implying the potency of the extract to orchestrate PI3K, which is the predominant signal for lessening the level of blood glucose. To verify these findings, in vivo studies were conducted, utilizing diabetic male albino rats treated with LPE-polyflavonoids and other groups treated with hesperidin and diosmin as single flavonoids. Our findings demonstrated that the LPE-polyflavonoids significantly ameliorated the levels of glucose, insulin, glycogen, liver function, carbohydrate metabolizing enzymes, G6Pd, and AGEs compared to the diabetic rats and those exposed to hesperidin and diosmin. Furthermore, the LPE-polyflavonoids regulated the TBARS, GSH, CAT, TNF-α, IL-1β, IL-6, and AFP levels in the pancreatic and hepatic tissues, suggesting their antioxidant and anti-inflammatory properties. In addition, the pancreatic and hepatic GLUT4 and GLUT2 were noticeably increased in addition to the pancreatic p-AKT in the rats administered with the LPE-polyflavonoids compared to the other diabetic rats. Remarkably, the administration of LPE-polyflavonoids upregulated the expression of the pancreatic and hepatic PI3K, AMPK, and FOXO1 genes, emphasizing the efficiency of the LPE in orchestrating all the signaling pathways necessitated to reduce the diabetes mellitus. Notably, the histopathological examinations of the pancreatic and hepatic tissues corroborated the biochemical results. Altogether, our findings accentuated the potential therapeutic role of LPE-polyflavonoids in controlling diabetes mellitus.